The Effect of Storyboard on Students’ Ability in Writing Narrative Text at the Tenth Grade of SMA Swasta Kampus Nommensen Pematangsiantar - Sinaga, Arni Wulandari; Herman, Herman; Situmeang, Siska Anggita (Lembaga Riset Mutiara Akbar, 2025)
This study examines the effect of using storyboard media on tenth-grade students’ ability to write narrative texts at SMA Swasta Kampus Nommensen Pematangsiantar. A quasi-experimental design was employed with two groups: an experimental class taught using storyboard media and a control class taught through conventional methods. Each group consisted of 20 students selected through purposive sampling. Data were collected through a pre-test and post-test writing assessment, focusing on content, organization, vocabulary, grammar, and mechanics. The results were analyzed using SPSS version 25, including descriptive statistics, normality and homogeneity tests, and paired and independent t-tests. Findings showed that the experimental group achieved a higher mean post-test score (78.75) compared to the control group (68.50). The significance value (p = 0.000) confirmed a meaningful difference between the groups. These results indicate that storyboard media effectively enhance students’ narrative writing skills, particularly in organizing ideas and maintaining structure, making it a valuable strategy in English language teaching.